Substitution of classic mechanism of extradition with European arrest warrant in European Union Criminal law - mohammad faraji (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2019)
It is possible to consider regional criminal law as the third domain of international criminal law beside two other domains including crimes with an exterior element and international crimes. European Union criminal law is the best example of a regional criminal law under which some organizations and regulations are provided in the Union level. Doing so, pursuant to the creation of a criminal jurisdiction in a regional level, different institutional and normative mechanisms are realized in order to prevent and suppress the crimes. This article is to explain European arrest warrant, as one of those aforementioned mechanisms, that based on mutual confidence and judicialization of the extradition procedure make simpler the surrender of accused or convicted persons than one related to extradition. To do so, concerned acts are analyzed in order to explain juridical nature and procedure of this warrant and also to make clear its differences with extradition. Consequently, execution of European arrest warrant instead of extradition, regarding to expansion of transnational criminality and simpler circulation of individuals amongst countries, can better realize criminal justice.